Research on Constriction Resistance of Drum Gear Coupling of High Speed EMU - Chunjun Chen; Xiang Zheng; Lu Yang; Linchun Zhou (Jixie chuandong)
In order to research the constriction resistance of the drum gear coupling of high speed EMU traction motor drive system，by using the geometrical analysis method，a mathematical model of the external tooth surface is established according to the structural parameters of the coupling. The relative angle of each tooth surface and the minimum clearance in the case of shaft inclination angle is calculated based on the coordinate transformation when there is an inclination between the shafts. Make use of the load distribution method to calculate the relationship between the load of each tooth and the total load of the coupling according to the flexural approximate differential equation of single tooth，according to the Hertz contact theory and the rough surface contact theory，the actual contact area and constriction resistance are calculated. The researches show that the inclination angle between the shafts is the extreme value when the minimum clearance of the tooth surface is zero. The greater the shaft inclination of the coupling，the greater the load on the single teeth，and the more uneven the load distribution on the tooth surface of different teeth. When the motor is in traction operation，the minimum actual contact area of the coupling is approximately 0.012 mm2，and the maximum is approximately 0.06 mm2. The total constriction resistance of the coupling is inversely proportional to the total torque. The coupling constriction resistance is between16.2 μΩ and 155.2 μΩ. The study of the constriction resistance can provide a certain theoretical reference for the analysis of the couplings galvanic corrosion in the future.